The Malangese Mask Wayang:The Process of Art Commodification at Asmorobangun Art Center, Pakisaji, Malang - Wibowo, Arining; Priyatna, Aquarini; Sobarna, Cece (KOMUNITAS: International Journal of Indonesian Society and Culture, 2019)
The article aims to describe the process of commodification of the Malangese Mask Wayang Art at Asmorobangun Art Center, Pakisaji Sub-district, Malang, Indonesia. Asmorobangun Art Center is one of the surviving art centers engaged in the efforts to preserve and develop the Malangese mask wayang art. The data used in this qualitative study were collected by means of interview, observation, and examination of relevant documents. The results show that the process of commodification of the Malangese mask wayang art manifests in three practices namely the gebyak senin-legian mask wayang performances, art tourism packaging, and mask production. Commodification has transformed the art into commodities/products that are part of the local tourism industry.